2022
DOI: 10.3389/fphar.2022.832707
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Protects Against Diabetes-Induced Cognitive Dysfunction by Inhibiting Mitochondrial Fission Protein DRP1

Abstract: Objectives: Diabetes is an independent risk factor for dementia. Mitochondrial dysfunction is a critical player in diabetes and diabetic complications. The present study aimed to investigate the role of mitochondrial dynamic changes in diabetes-associated cognitive impairment.Methods: Cognitive functions were examined by novel object recognition and T-maze tests. Mice hippocampi were collected for electron microscopy and immunofluorescence examination. Neuron cell line HT22 and primary hippocampal neurons were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 76 publications
1
9
0
2
Order By: Relevance
“…Compound structures with neurotoxic potential, given in Figure 1, fit to the 4) with fitting-points on both purine and furan rings. Streptozotocin (7) a glucosamine-nitrosourea structure, provides the same fits as glucose (5,6) and these fitting-points are shared by ethidium (12). In contrast to the fits of glucose, those of pentylenetetrazole (8,9) do not overlap.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Compound structures with neurotoxic potential, given in Figure 1, fit to the 4) with fitting-points on both purine and furan rings. Streptozotocin (7) a glucosamine-nitrosourea structure, provides the same fits as glucose (5,6) and these fitting-points are shared by ethidium (12). In contrast to the fits of glucose, those of pentylenetetrazole (8,9) do not overlap.…”
Section: Resultsmentioning
confidence: 99%
“…MPTP (1-methyl-4phenyl-1,2,3,6-tetrahydropyridine) [26], paraquat [26], rotenone [26], ethidium bromide [27], cuprizone [28], 3-nitro-L-tyrosine [29], streptozotocin [30], pentylenetetrazole (PTZ) [31], metamphetamine [32], lysophosphatidylcholine [33], sphingosine [34]. Compounds providing protection against experimentally induced diabetes and β-cell apoptosis: loganin [1], taurine [2], silibinin [3], 17β-estradiol [6], vitamin D3 [7], mdivi-1 [12], metformin [12], gliclazide [35], nicotinamide [36], telmisartan [37]. Compounds providing protection against apoptosis in animal models of Parkinson's and MS respectively: ursolic acid [26], astilbin [26], β-lapachone [26], papaverine [26], embelin [26], dexrazoxane [26], schisandrin A [26], 20-hydroxyecdysone [38], NE52-QQ57 [39]; magnol [40], cannabidiol [41], monomethylfumarate [42], glucosylceramide [43].…”
Section: Compound Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Dynamin 1-like protein (drp1) was also found in this group; its function is to regulate mitochondrial fission [ 40 ]. It was reported that metformin can suppress excessive mitochondrial fission by inhibiting drp1 protein activity and restoring mitochondrial homeostasis in diabetic mice [ 41 ]. Son of sevenless protein 1 (SOS1) is involved in the tyrosine phosphorylation of insulin receptor substrate 1 (IRS1) in the insulin signaling pathway [ 42 ].…”
Section: Discussionmentioning
confidence: 99%